PENGEMBANGAN MEDIA KALENDER KARTU BACA DALAM MENINGKATKAN KETERAMPILAN MEMBACA PERMULAAN DI SEKOLAH DASAR - Tisnasari, Sundawati; Yuliana, Rina; Nuraeni, Hani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research aims to develop learning media in the form of a Reading Card Calendar and to determine the feasibility and response of students to the use of this media in improving initial reading skills in elementary school. This research uses the Research and Development (R&D) method with the ADDIE model which covers the stages of analysis, design, development, implementation, and evaluation. This research was carried out in grade 1 of SDN CurugKota Serang, Banten with the research subject of grade 1 students. The results of the study show that the Reading Card Calendar media developed has met valid criteria based on the assessment of material experts, media experts, and language experts. In addition, the results of limited trials show that this media is practically used in learning and receives a positive response from students. The use of the Reading Card Calendar media is able to increase students' interest, motivation, and involvement in initial reading activities. Thus, the Reading Card Calendar media is suitable to be used as an alternative learning media to improve initial reading skills in elementary school students.